Unusually long duration and delayed penetrance in a family with FTD and mutation in MAPT (V337M). Issue 1 (16th March 2016) - Domoto‐Reilly, Kimiko; Davis, Marie Y.; Keene, C. Dirk; Bird, Thomas D.
Abstract : Mutations in the MAPT gene coding for the tau protein are one of the most common causes of familial frontotemporal dementia (FTD). In a previously described family with the V337M mutation in MAPT, we now report an affected woman who died at age 92 with a >40 year duration of symptoms, more than three times the mean disease duration in her family (13.8 years). Neuropathology showed the typical findings of a diffuse tauopathy. Conversely, her 67‐year‐old son with the same mutation remains asymptomatic more than 15 years beyond the mean age of onset in the family (51.5 years). These two cases demonstrate the marked variability in onset and duration of familial FTD and underscore the difficulties of discussing these issues with patients and families. The presumed genetic and environmental factors influencing these parameters remain largely unknown. © 2016 Wiley Periodicals, Inc.